Vegetative roughness estimation for hydraulic modelling: a review - Zahidi, Izni; Yusuf, Badronnisa; Cope, Mike (2014)
The application of hydrodynamic models for simulating the overbank flow patterns and predicting flood water levels in rivers and floodplains have improved significantly over recent years. However, roughness remains a huge uncertainty which cannot be directly measured. This is especially the case for vegetation growth in watercourses and on floodplains which significantly influence the behaviour of a fluvial system through the reduction of flow conveyance. Therefore, it is crucial to understand how the vegetation element can be represented better in the hydrodynamic model. This paper follows the development of vegetative roughness estimation for hydraulic modeling through laboratory experiments and remote sensing. The study concludes that there is a prospect of utilizing data fusion of remote sensing data to accurately estimate the main vegetation properties such as height and density as a parameter to input to calculations of surface roughness for practical applications.